Isolation and identification of fungi from outer surface of cockroach Periplaneta americana collected from AL-Diwaniya educational general hospital and study of some virulence factors. - H. Al-galebi, Haider (University of Thi-Qar Journal of Science, 2019)
Fourteen fungal species were isolated from outer surface of 50 specimens of American cockroaches collected from different places in AL-Diwaniya educational general hospital (wards, Kitchen, pathways, and water cycles) during Autumn 2008. Fungi represented by three species of dermatophytes (Trichophyton mentagrophytes, Microsporum gypseum and Trichophyton rubrum) and eleven species of other fungi. However, high frequency was expressed by Aspergillus flavus (18.51%) and less frequency was T. mentagrophytes (2.11%). Some fungi were screened for the aflatoxin production, Hemolysis ability and activity of phospholipase. The results showed that all of fungi isolated have ability to aflatoxin production except M. gypseum, T. rubrum and C. albicans. Whereas the results of Hemolysis ability on blood agar revealed that all of fungi have ability to hemolyze blood except C. albicans and Trichophyton rubrum, and highest of hemolysis ability was Asp. fumigatus and less was Mirosporum gypseum. The results show too, that the C. albicans was high phospholipase activity, and in second grade was Asp. flavus, whereas Asp. fumigatus, M. gypseum, T. rubrum and Alternaria alternata record less enzymatic activity.